2008
DOI: 10.1590/s0004-27302008000900007
|View full text |Cite
|
Sign up to set email alerts
|

Bone and heart abnormalities of subclinical hyperthyroidism in women below the age of 65 years

Abstract: The objective of the present study was to evaluate bone and cardiac abnormalities and symptoms and signs of thyroid hormone excess in women with subclinical hyperthyroidism (SCH) aged < 65 years. Forty-eight women with SCH were evaluated. The control group consisted of 48 euthyroid volunteers. The mean symptom rating scale score was signifi cantly higher in patients. Cardiac involvement, both morphological and affecting systolic and diastolic functions, was also observed in patients. Women with SCH showed a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 9 publications
0
17
1
3
Order By: Relevance
“…Similarly, small studies of have found either no change (Foldes et al 1993, Gurlek & Gedik 1999, Ugur-Altun et al 2003, Lee et al 2006 or a small reduction in BMD (Tauchmanova et al 2004, Rosario 2008 in pre-menopausal women with subclinical hyperthyroidism. By contrast, the majority of studies in postmenopausal women demonstrated a reduction in BMD (Foldes et al 1993, Mudde et al 1994, Tauchmanova et al 2004, Lee et al 2006, Belaya et al 2007, Rosario 2008.…”
Section: Endogenous Subclinical Hyperthyroidismmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, small studies of have found either no change (Foldes et al 1993, Gurlek & Gedik 1999, Ugur-Altun et al 2003, Lee et al 2006 or a small reduction in BMD (Tauchmanova et al 2004, Rosario 2008 in pre-menopausal women with subclinical hyperthyroidism. By contrast, the majority of studies in postmenopausal women demonstrated a reduction in BMD (Foldes et al 1993, Mudde et al 1994, Tauchmanova et al 2004, Lee et al 2006, Belaya et al 2007, Rosario 2008.…”
Section: Endogenous Subclinical Hyperthyroidismmentioning
confidence: 99%
“…Small studies of patients with subclinical hyperthyroidism have reported conflicting results either describing normal (De Menis et al 1992, Faber et al 1994, Mudde et al 1994, Gurlek and Gedik 1999, Lee et al 2006 or elevated (Campbell et al 1996, Kumeda et al 2000, Tauchmanova et al 2004, Belaya et al 2007, Rosario 2008) bone turnover makers. Similarly, small studies of have found either no change (Foldes et al 1993, Gurlek & Gedik 1999, Ugur-Altun et al 2003, Lee et al 2006 or a small reduction in BMD (Tauchmanova et al 2004, Rosario 2008 in pre-menopausal women with subclinical hyperthyroidism. By contrast, the majority of studies in postmenopausal women demonstrated a reduction in BMD (Foldes et al 1993, Mudde et al 1994, Tauchmanova et al 2004, Lee et al 2006, Belaya et al 2007, Rosario 2008.…”
Section: Endogenous Subclinical Hyperthyroidismmentioning
confidence: 99%
“…Subclinical thyrotoxicosis is associated with bone mass compromise, especially among postmenopausal women (57,58,133), and morphological and functional heart disorders (57,58), which have more clinical repercussions among older adults. To minimize the adverse effects of suppressive therapy with T4, some steps are important.…”
Section: What Is the Indicated Tsh Level Following Initial Treatment?mentioning
confidence: 99%
“…One of the repercussions of SCH is a decline of bone mineral density (BMD), notably in postmenopausal women and in patients with TSH ≤ 0.1 mIU/L (1,6). However, few studies have evaluated the effect of treatment of SCH on bone metabolism and bone mass (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%